KARAKTERISTIK PEDAGANG PISANG DI PASAR WATES WETAN KECAMATAN RANUYOSO KABUPATEN LUMAJANG - Masyita, Syifani Putri; Sofia, Sofia (Fakultas Pertanian Universitas Jember, 2020)
Wates Market Wetan is one of the markets that has a lot of banana trading activity. The dense trading activity at Wates Wetan Market has caused congestion on the roads of Probolinggo and Lumajang Regencies. This study aims to determine the characteristics of banana traders in Wates Wetan Market, Ranuyoso District, Lumajang Regency. The research method used is a qualitative method. The research location was determined purposively, namely in Wates Wetan Market. Determination of informants was done through purposive sampling then snowball. Data collection techniques by means of interviews, observation and documentation. The data analysis method used the interactive model of Miles and Huberman. The validity of the data used source triangulation and technique triangulation. The results showed that: the characteristics of banana traders were divided into two, namely internal characteristics and external characteristics. The internal characteristics found in banana traders in Wates Wetan Market include banana traders who are at the productive age for work, low education level, have 3-6 family dependents, in general banana traders at Wates Wetan Market are male. The external characteristic of banana traders at Wates Wetan Market is that banana traders are mostly collectors and some are wholesalers. Banana traders make trading bananas their main job. The types of bananas that are traded are various, such as Raja Banana, Mas Banana, Raja Jackfruit Banana, Barlin Banana, Kepok Banana, Milk Banana, Ambon Banana, Green Banana and Embuk Banana. Banana traders usually come during the market, but there are also banana traders who come every day at Wates Wetan Market, generally they come from early morning. Most of the banana traders use motorbikes to come to the Wates Wetan Market. Keywords: Characteristics, traders